Nationhood and women in postcolonial African literature - Hungwe, Elda; Hungwe, Chipo (Purdue University Press, 2015)
In their article "Nationhood and Women in Postcolonial African Literature" Elda Hungwe and Chipo Hungwe, through an analysis of Pepetela's Mayombe, Achebe's Anthills of the Savannah, and Ngugi's Petals of Blood discuss nationhood and nation in postcolonial African literature within the framework of the postcolonial theory. Postcolonial theory negates master narratives of nation and nationhood, hence it deconstructs such narratives as problematic. Hungwe and Hungwe discuss problems associated with definitions of nation where groups or members are peripheralized. While Hungwe and Hungwe acknowledge that nationalism served a critical role during decolonization, their conclusion is that in postcolonial Africa notions of nation and nationhood represent problematic issues with regard to ethnicity and gender and that globalization in particular impacts and challenges the notion of nation and nationhood.